Towards computational polar-topotronics: Multiscale neural-network quantum molecular dynamics simulations of polar vortex states in SrTiO3/PbTiO3 nanowires - Linker, Thomas; Fukushima, Shogo; Kalia, Rajiv K.; Krishnamoorthy, Aravind; Nakano, Aiichiro; Nomura, Ken-ichi; Shimamura, Kohei; Shimojo, Fuyuki; Vashishta, Priya (Frontiers in Nanotechnology, 2022)
Recent discoveries of polar topological structures (e.g., skyrmions and merons) in ferroelectric/paraelectric heterostructures have opened a new field of polar topotronics. However, how complex interplay of photoexcitation, electric field and mechanical strain controls these topological structures remains elusive. To address this challenge, we have developed a computational approach at the nexus of machine learning and first-principles simulations. Our multiscale neural-network quantum molecular dynamics (NNQMD)/molecular mechanics (MM) approach achieves orders-of-magnitude faster computation, while maintaining quantum-mechanical accuracy for atoms within the region of interest. This approach has enabled us to investigate the dynamics of vortex states formed in PbTiO3 nanowires embedded in SrTiO3. We find topological switching of these vortex states to topologically trivial, uniformly polarized states using electric field and trivial domain-wall states using shear strain. These results, along with our earlier results on optical control of polar topology, suggest an exciting new avenue toward opto-electro-mechanical control of ultrafast, ultralow-power polar topotronic devices.